12(x+4)=-4(2x-12)

Simple and best practice solution for 12(x+4)=-4(2x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(x+4)=-4(2x-12) equation:



12(x+4)=-4(2x-12)
We move all terms to the left:
12(x+4)-(-4(2x-12))=0
We multiply parentheses
12x-(-4(2x-12))+48=0
We calculate terms in parentheses: -(-4(2x-12)), so:
-4(2x-12)
We multiply parentheses
-8x+48
Back to the equation:
-(-8x+48)
We get rid of parentheses
12x+8x-48+48=0
We add all the numbers together, and all the variables
20x=0
x=0/20
x=0

See similar equations:

| -15=-5vv= | | 2(6v+1)=27+7v | | z^2–30z=-31 | | 3n-7n+5=-8n+45-4n | | z2–30z=-31 | | 144+19m=467 | | −0.75p−2=0.25p= | | 10x+4+x^2+11+90=180 | | 3/8b-1/4=5/16 | | 47+8x=2+7(3x-6) | | x/5=x+1/7 | | 2d-3=15 | | 17=-6k+5+6 | | 7+2x+4=25 | | 10x-6+53=16x+11 | | (7+3t)/4=-8t | | x/2-x/8=5 | | 13x-34=56 | | 6x+24=8x-6 | | -5t-2(5t-12)=100 | | 3n-7n+5=8n+45-4n | | 12-5n=-3(-7n-4) | | -2-8i-4-3i=-6-11i | | 7x-2+11x-2+48=180 | | 1.1v−1.8=7.3 | | 4(2+7x)=-20 | | 36n-128=448 | | 5m+9=-16 | | -4(8+5x)=10+x | | 3i-i=2i | | −5(x+3)=20 | | 6x+3=5x-2=39 |

Equations solver categories